Biomarkers for diabetic retinopathy - Maria V. Budzinskaya; Dmitry V. Lipatov; Vladislav G. Pavlov; Denis V. Petrachkov (Сахарный диабет, 2020)
A data analysis on the actual direction of biomedicine, the study of biomarkers in diabetic retinopathy (DR), was done. Biomarkers identification is important for screening, diagnosis, monitoring, prevention and prediction of the clinical response of the patient to the treatment. In addition, studying the biomarkers allows increase of the effectiveness and safety of using various treatment options. The review examines two main groups of biomarkers, molecular and visualised, which shows the current state of the problem and the prospects for studying biomarkers in the context of the DR treatment. Nowadays, searching for and finding new biomarkers is important and will allow us to develop individual treatment regimens for DR and personalised medicine in an interdisciplinary aspect: ophthalmology and endocrinology.